2010
DOI: 10.1371/annotation/12224797-353c-4e9c-92f3-a0de9b527415
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Rad21-Cohesin Haploinsufficiency Impedes DNA Repair and Enhances Gastrointestinal Radiosensitivity in Mice

Abstract: Approximately half of cancer-affected patients receive radiotherapy (RT). The doses delivered have been determined upon empirical experience based upon average radiation responses. Ideally higher curative radiation doses might be employed in patients with genuinely normal radiation responses and importantly radiation hypersensitive patients would be spared the consequences of excessive tissue damage if they were indentified before treatment. Rad21 is an integral subunit of the cohesin complex, which regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…There are a number of mechanistic links between MYC, RAD21, BETs, and CHK1. MYC and RAD21 play a role in RS and the DNA damage response (DDR) pathways [92,93]. MYC, a transcription factor involved in the pathogenesis of OS, has been known to be overexpressed and amplified in localized and metastatic OS, and contributes to therapeutic resistance of the disease [47,94].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of mechanistic links between MYC, RAD21, BETs, and CHK1. MYC and RAD21 play a role in RS and the DNA damage response (DDR) pathways [92,93]. MYC, a transcription factor involved in the pathogenesis of OS, has been known to be overexpressed and amplified in localized and metastatic OS, and contributes to therapeutic resistance of the disease [47,94].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Rad21 mutant cells have been shown to be defective in HR [11], and haploinsufficiency of Rad21 in mice induces impairment of DDR. This demonstrated that Rad21 is critical in promoting HR-mediated DNA damage repair [12].…”
Section: Introductionmentioning
confidence: 94%
“…RAD21 is believed to function in sister chromatid alignment as part of the cohesin complex. By holding sister chromatids together, RAD21 and the cohesin complex can facilitate the repair of DNA damage incurred during DNA replication [11,12]. Therefore, we asked whether rad21a haploinsufficiency, which prevents ALT, was accompanied by a change of telomeric DNA damage, possibly through DNA damage repair by HR.…”
Section: Rad21;ras Brain Tumors Show An Increase In γH2ax Tifs But Have Normal Tert Levels and Rad51 Focimentioning
confidence: 99%
“…Cohesin-deficient cancers cells have increased sensitivity to ionizating radiation, owing to cohesin's role in DNA double-strand break repair [15,193]. Therefore, using DNAdamaging agents to further block the compromised DNA repair pathway of cohesin mutant cells has potential for selective inhibition of these cells (Figure 3).…”
Section: Dna-damaging Agentsmentioning
confidence: 99%